Model Pembelajaran Tari Kreatif untuk Meningkatkan Percaya Diri Anak Usia Taman Kanak-Kanak - I Gusti Komang Aryaprasta; Arie Rakhmat Riyadi (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2018)
AbstractThis research is motivated by the need for the stimulation of early childhood development. Various aspects of child development, including social-emotional learning methods that are appropriate to the characteristics of child development. Confidence in children is an integral part of primary education, especially early childhood education. Various learning approaches should be able to boost it to increase optimally developed. Dance learning that has been identical to train the things that are physiological was identified to have advantages regarding the formation of the child's personality. The purpose of this study is to develop creative dance learning tools that are expected to increase the confidence of children, especially children of kindergarten age (TK). Research method using action research/action research as much as three cycles. Research subjects are kindergarten children consisting of two kindergartens, the kindergarten Labschool UPI and Kartika Candra Gegerkalong Kindergarten. The results of this study in addition to creative dance learning devices are tested, also proves creative dance learning can increase the confidence of kindergarten children.Keywords: Dance, Creative, Creativity, Confidence, Learning, And Kindergarten Children. Abstrak Penelitian ini dilatarbelakangi oleh kebutuhan stimulasi perkembangan anak usia dini. Beragam aspek perkembangan anak termasuk sosial-emosional memerlukan metode pembelajaran yang sesuai dengan karakteristik perkembangan anak. Rasa percaya diri pada anak merupakan bagian penting dalam pendidikan dasar, khususnya pendidikan usia dini. Beragam pendekatan pembelajaran harus mampu mengdongkrak hal tersebut agar meningkat ditumbuh-kembangkan secara optimal. Pembelajaran tari yang selama ini identik melatih hal-hal yang bersifat fisiologis ternyata diidentifikasi memiliki kelebihan dalam hal pembentukan kepribadian anak. Tujuan penelitian ini adalah untuk mengembangkan perangkat pembelajaran tari kreatif yang diharapkan dapat meningkatkan rasa percaya diri anak, khususnya anak usia taman kanak-kanak (TK). Metode penelitian menggunakan penelitian tindakan/ action research sebanyak 3 siklus. Subjek penelitian adalah anak TK Labschool UPI. Hasil penelitian ini selain perangkat pembelajaran tari kreatif yang teruji, juga membuktikan pembelajaran tari kreatif dapat meningkatkan percaya diri anak usia TK. Kata Kunci: tari, kreatif, kreativitas, percaya diri, pembelajaran, dan anak TK.